1996
DOI: 10.1074/jbc.271.30.17704
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epithelial Sodium Channels by Short Actin Filaments

Abstract: Cytoskeletal elements play an important role in the regulation of ion transport in epithelia. We have studied the effects of actin filaments of different length on the ␣, ␤, ␥-rENaC (rat epithelial Na ؉ channel) in planar lipid bilayers. We found the following. 1) Short actin filaments caused a 2-fold decrease in unitary conductance and a 2-fold increase in open probability (P o ) of ␣,␤,␥-rENaC. 2) ␣,␤,␥-rENaC could be transiently activated by protein kinase A (PKA) plus ATP in the presence, but not in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
81
1
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 52 publications
7
81
1
1
Order By: Relevance
“…ARP3 and Coronin 1A, both of which increase actin filament assembly, 30,31 are decreased specifically during abstinence. Taken together, this would suggest a decrease in actin polymerization during abstinence which could alter potassium, 32 sodium, 33 calcium, AMPA, 34 and NMDA receptor channel function. 35 Owing to its regulation of receptor functionality, actin polymerization regulation can affect the potentiation or depression of a neuron.…”
Section: Discussionmentioning
confidence: 95%
“…ARP3 and Coronin 1A, both of which increase actin filament assembly, 30,31 are decreased specifically during abstinence. Taken together, this would suggest a decrease in actin polymerization during abstinence which could alter potassium, 32 sodium, 33 calcium, AMPA, 34 and NMDA receptor channel function. 35 Owing to its regulation of receptor functionality, actin polymerization regulation can affect the potentiation or depression of a neuron.…”
Section: Discussionmentioning
confidence: 95%
“…Some data suggest that actin may interact directly with ion channels. For example, short actin filaments enhanced sodium channel activity in planar lipid bilayers, and cytochalasin D blocked the effect of the actin filaments (Berdiev et al, 1996). On the other hand, there are a number of actin-binding proteins that link actin with membranes, and some such proteins (e.g., dystrophin) have been implicated in modulating calcium influx (for review, see Hartwig, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that, in addition to their roles in regulating cell structure and motility, actin filaments may f unction in the modulation of ion channel f unction. The evidence is based on pharmacological data showing that the actin filament-disrupting agent cytochalasin D can alter ion flux through Na ϩ channels (C antiello et al, 1991;Undrovinas et al, 1995;Berdiev et al, 1996), voltage-dependent calcium channels (VDCC) (Johnson and Byerly, 1993), and NMDA receptor channels (Rosenmund and Westbrook, 1993). Whether actin normally plays roles in regulating Ca 2ϩ influx in physiological and pathophysiological settings is unknown.…”
mentioning
confidence: 99%
“…Nonetheless, the mechanosensitivity of ENaC remains a matter of controversy despite a variety of studies attempting to address this issue. Examples of studies in which ENaC appears to be stretch sensitive include the observations that the purified renal ENaC in planar lipid bilayer membranes can be activated by hydrostatic pressure (1,4,8) and that expression of ␣-ENaC in mammalian cells results in stretch-activated channel activity (10). Recent studies have shown that osmotic stretch regulates rat ␣-, ␤-, and ␥-ENaC expressed in Xenopus laevis oocytes (9).…”
mentioning
confidence: 99%